The Effect of Using Digital Storytelling on Students' English Narrative Writing Skills of Eleventh Grade at SMAN 1 Pantai Labu - Amelia, Indah; Zulfitri, Zulfitri (Universitas Negeri Medan, 2024)
The aim of this research is to obtain empirical evidence about the effect of Digital Storytelling on students' English narrative writing skills. The object of this research was 150 class XI students of SMAN 1 Pantai Labu which was carried out in August 2023. The research method was quasi-experimental. The sampling technique is purposive sampling; it was conducted in class XI at SMAN 1 Pantai Labu class XI MIA 2 as an experimental class while class XI IIS 2 as a control class. Both the experimental class and the control class consisted of 30 students. The instrument used in this research was a writing test. There is a pre-test and post-test on writing narrative texts given to students. Data was obtained in this research by statistical calculations. Based on the research results, the researcher concluded that the narrative writing ability of class XI students at SMAN 1 Pantai Labu in the experimental class was good. The highest score on the post-test was 70 (4 students) and the lowest score on the post-test was 50 (5 students). The writing ability of students in the control class is sufficient. The highest score on the post test was 85 (5 students) and the lowest score on the post test was 60 (1 student). From the findings, the description of the mean score of the students™ pre-test and post-test of experimental class showed improvement. The mean score of pre-test and post-test of experimental class were 65.67 and 74.33 which showed improvement. The data showed that the use of Digital Storytelling in teaching the students™ writing skill especially in narrative is effective.